The Noradrenergic System of Aged GDNF Heterozygous Mice - V. Zaman; Z. Li; L. Middaugh; S. Ramamoorthy; B. Rohrer; M. E. Nelson; A. C. Tomac; B. J. Hoffer; G. A. Gerhardt; A. Ch. Granholm DR. (Cell Transplantation, 2003)
Glial cell line-derived neurotrophic factor (GDNF) is a trophic factor for noradrenergic (NE) neurons of the pontine nucleus locus coeruleus (LC). Decreased function of the LC-NE neurons has been found during normal aging and in neurodegenerative disorders. We have previously shown that GDNF participates in the differentiation of LC-NE neurons during development. However, the continued role of GDNF for LC-NE neurons during maturation and aging has not been addressed. We examined alterations in aged mice that were heterozygous for the GDNF gene (Gdnf+/–). Wild-type (Gdnf+/+) and Gdnf+/– mice (18 months old) were tested for locomotor activity and brain tissues were collected for measuring norepinephrine levels and uptake, as well as for morphological analysis. Spontaneous locomotion was reduced in Gdnf+/– mice in comparison with Gdnf+/+ mice. The reduced locomotor activity of Gdnf +/– mice was accompanied by reductions in NE transporter activity in the cerebellum and brain stem as well as decreased norepinephrine tissue levels in the LC. Tyrosine hydroxylase (TH) immunostaining demonstrated morphological alterations of LC-NE cell bodies and abnormal TH-positive fibers in the hippocampus, cerebellum, and frontal cortex of Gdnf+/– mice. These findings suggest that the LC-NE system of Gdnf+/– mice is impaired and suggest that GDNF plays an important role in continued maintenance of this neuronal system throughout life.